2022
DOI: 10.1002/jwmg.22207
|View full text |Cite
|
Sign up to set email alerts
|

Methodology matters when estimating deer abundance: a global systematic review and recommendations for improvements

Abstract: Deer (Cervidae) are key components of many ecosystems and estimating deer abundance or density is important to understanding these roles. Many field methods have been used to estimate deer abundance and density, but the factors determining where, when, and why a method was used, and its usefulness, have not been investigated. We systematically reviewed journal articles published during 2004–2018 to evaluate spatio‐temporal trends in study objectives, methodologies, and deer abundance and density estimates, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 87 publications
(149 reference statements)
2
56
2
Order By: Relevance
“…It is particularly valuable when target populations inhabit densely vegetated terrain that is difficult to survey using visual counts of animals, as is often the case for sambar deer ( Leslie 2011 ). A global systematic review of over 5,000 deer abundance and density estimates concluded that mark–recapture surveys using camera traps provided greater precision, on average (mean CV( ) = 0.39), than other survey methods for which sufficient data were available ( Forsyth et al 2022 ). Eleven of our 12 surveys provided greater precision than this average, with seven surveys attaining CV( ) ≤ 0.25.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is particularly valuable when target populations inhabit densely vegetated terrain that is difficult to survey using visual counts of animals, as is often the case for sambar deer ( Leslie 2011 ). A global systematic review of over 5,000 deer abundance and density estimates concluded that mark–recapture surveys using camera traps provided greater precision, on average (mean CV( ) = 0.39), than other survey methods for which sufficient data were available ( Forsyth et al 2022 ). Eleven of our 12 surveys provided greater precision than this average, with seven surveys attaining CV( ) ≤ 0.25.…”
Section: Discussionmentioning
confidence: 99%
“…The relative use of each method has varied regionally and temporally. Counts of deer or their sign from terrestrial or aerial transects have been most common in recent years ( Forsyth et al 2022 ). However, the use of camera traps for deer surveys has increased since the 2000s, particularly in North America ( Forsyth et al 2022 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the PO and PA data introduced above, we gathered hunting culling returns from the National Park & Wildlife Service (NPWS, https://www.npws.ie/), responsible for issuing hunting licences. Culling returns are an alternative source of data (Milner et al 2006, Forsyth et al 2022, and we retained this dataset to validate the ISDMs we built by integrating PO and PA data.…”
Section: Studied Speciesmentioning
confidence: 99%